2019
DOI: 10.1093/qmathj/haz046
|View full text |Cite
|
Sign up to set email alerts
|

Bogomolov Multipliers of P-Groups of Maximal Class

Abstract: Let G be a p-group of maximal class and order p n . We determine whether of not the Bogomolov multiplier B 0 (G) is trivial in terms of the lower central series of G and P 1 = C G (γ 2 (G), γ 4 (G)). If in addition G has positive degree of commutativity and P 1 is metabelian, we show how understanding B 0 (G) reduces to the simpler commutator structure of P 1 . This result covers all p-groups of maximal class of large enough order and, furthermore, it allows us to give the first natural examples of p-groups wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Whereas the Bogomolov multiplier vanishes on finite simple groups [55] and simple Lie algebras (follows from the results of Peggy Batten's PhD thesis [6] where the vanishing of the Schur multiplier of simple Lie algebras is proven), on the other extreme edge (pgroups/nilpotent Lie algebras) there are nontrivial examples. For instance, in the paper [29] Gustavo Fernández-Alcober and Urban Jezernik showed that the Bogomolov multiplier of a p-group can be as large as we wish. In the papers [75,76] mentioned above, one can find examples of finite-dimensional nilpotent Lie algebras with nontrivial Bogomolov multiplier.…”
Section: It Is Based On the Notion Of Nonabelian Exterior Squarementioning
confidence: 85%
“…Whereas the Bogomolov multiplier vanishes on finite simple groups [55] and simple Lie algebras (follows from the results of Peggy Batten's PhD thesis [6] where the vanishing of the Schur multiplier of simple Lie algebras is proven), on the other extreme edge (pgroups/nilpotent Lie algebras) there are nontrivial examples. For instance, in the paper [29] Gustavo Fernández-Alcober and Urban Jezernik showed that the Bogomolov multiplier of a p-group can be as large as we wish. In the papers [75,76] mentioned above, one can find examples of finite-dimensional nilpotent Lie algebras with nontrivial Bogomolov multiplier.…”
Section: It Is Based On the Notion Of Nonabelian Exterior Squarementioning
confidence: 85%
“…It follows from the above proofs that when the uniform subgroup of G is abelian, the group SK 1 (Z p G ) is of finite exponent bounded in terms of the rank of G, and so it is a finite p-group. This is the case, for example, when G is a pro-p group of finite coclass (see [12,Theorem 10.1] and [17,Theorem 4.4]).…”
Section: Exterior Squares and Commutator Relationsmentioning
confidence: 99%
“…Most p groups of maximal class have non-trivial Bogomolov multiplier (cf. [10]), but Conjecture 1 holds for p groups of maximal class. On the other hand, the Bogomolov multiplier is trivial for all cyclic groups, but Noether's Rationality problem does not hold for all cyclic groups.…”
mentioning
confidence: 99%